PERSONALITY TRAITS AS PREDICTORS OF DEMOTIVATION IN ENGLISH LANGUAGE LEARNING: A QUANTITATIVE ANALYSIS (Contemporary Journal of Social Science Review, 2025)
Despite studying the English language in colleges, Pakistani students’ English language proficiency level is still lagging behind. Prior research indicates that demotivation is a major cause of language learning failure in many EFL classrooms. To this end, the present research primarily aims at examining the L2 demotivation concept in relation to the big-five personality dimensions (i.e., conscientiousness, agreeableness, openness to experience, extraversion, and neuroticism). The present study adopted a a quantitative m research design to answer the proposed research questions.  This study adopted questionnaires on L2 demotivation and big-five personality traits. To analyse the data, descriptive statistics, Pearson correlation, and multiple linear regressions tests were performed in the SPSS (Version, 24). The findings revealed the existence of L2 demotivation among EFL students that was the result of both external and internal factors: characteristics of classes, class environment, class materials, lack of interest in the English language, and experiences of failures. Additionally, the results also highlighted that of the five personality dimensions, the conscientiousness personality trait had a significant and negative impact on all six causes of demotivation (i.e., teacher behaviors, characteristics of classes, class environment, class materials, lack of interest, and experiences of failure) among college students, whereas openness to experience personality trait showed its significant and negative impact on the factors that caused demotivation among college students, except for experience of failure as a cause of demotivation. The overall results garnered in the present study suggest that Pakistani EFL teachers, higher authorities in education, and language-in-education policymakers need to take necessary actions to address the causes that debilitate EFL learners' motivation.